A singular scholar and writer in a profoundly racist world. Issue 8 (20th June 2016) - Bulmer, Martin
ABSTRACT: W.E.B. Du Bois was a remarkable pioneer, and Aldon Morris does justice to his career and significance. The nature of the racist world which he inhabited is convincingly evoked, and his claim to be a founding father of American sociology is well argued. Yet in 1910 Du Bois abandoned academia to become the founding editor of the NAACP magazine THE CRISIS, and towards the end of his life four decades later abandoned the USA to live in Ghana. Was Du Bois at heart the sociologist trained as a graduate student in Berlin, or did he become something different, an advocate, investigator and prophet who from a lofty and austere pinnacle addressed his compatriots about what it meant to be black in America?